ISOLASI MINYAK ATSIRI BUNGA MELATI DALAM SEDIAAN MINYAK AROMATERAPI UNTUK MENGURANGI KECEMASAN PADA IBU NIFAS - Venny Diah; Lia Fitria; Siti Nurrosyidah (Poltekkes Kemenkes Medan, 2022)
The birth of a baby should bring joy, but for some women giving birth can be stressful so that it has a physical, social, and psychological impact. One of the psychological aspects that affect postpartum is anxiety. Non-pharmacological therapies that can be used are massage therapy, acupuncture, acupressure, music therapy, yoga, tai chi, hypnotherapy, prayer therapy, and aromatherapy. Aromatherapy that is often used includes sandalwood, jasmine, basil, cloves, lavender, cinnamon. The purpose of this study was to isolate jasmine essential oil to be used as aromatherapy candles to reduce anxiety in postpartum mothers. This research is an experimental laboratory research. Jasmine essential oil contains alkaloids, flavonoids, saponins, steroids/terpenoids. Isolation of essential oils took 3 hours with the temperature of the first drop of 85oC and a % yield of 2,0602%. Jasmine essential oil has the characteristics of a liquid form, white in color, has a distinctive jasmine odor, and has a bitter taste. Jasmine flower essential oil also showed positive results when tested with Sudan III reagent. Keywords: anxiety; jasmine essential oi